Measuring climate change vulnerability: a comparison of two indexes - Urothody, AA; Larsen, HO (Banko Janakari, 2010)
Climate change is predicted and currently observed to especially affect the rural poor, and some sort of support for adaptation is relevant. This paper tests two vulnerability assessment indexes in Lete and Kunjo VDCs in Mustang District: the Livelihood Vulnerability Index (LVI) and the Livelihood Effect Index (LEI). The indexes are completed based on primary data from 60 randomly selected respondents and the vulnerabilities at VDC and household levels are assessed. The figures resulting from the vulnerability assessments correspond with contextual information from the area elicited during key informant interviews and the methods are concluded useful in a Nepalese context. Both indexes validly reflect the relative differences between the two VDCs in terms of vulnerability to climate change impacts and factors contributing to it and both could therefore usefully form the basis for a nationally applicable index to identify and prioritise mitigation needs. However, a number of challenges to using indexes and basing them on respondents’ perceptions are recognised. Key words: Climate change; livelihoods; Mustang; vulnerability DOI: 10.3126/banko.v20i1.3503 Banko Janakari, Vol. 20, No. 1 pp.9-16